2023
DOI: 10.1002/bbb.2481
|View full text |Cite
|
Sign up to set email alerts
|

Progress and development of syngas fermentation processes toward commercial bioethanol production

Abstract: Syngas is created through the thermochemical conversion of biomass using gasification or pyrolysis and from CO‐rich off‐gases obtained from industries such as steel mills. The Wood–Ljungdahl metabolic pathway, or one of its variations, is used by acetogenic bacteria to convert syngas components (CO, H2, and CO2) to alcohols and other compounds. Many factors affect how well syngas is fermented, including the bacteria species used, syngas composition, medium components, bioreactor type, operational parameters us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…As the uctuations in the pressure through the hollow ber lumen and the membrane's surface area per unit working volume of the liquid inuence the gas-liquid k La , 115 a study has reported that with a lower pressure of 37.23 kPa and a larger membrane surface area per unit working volume AS/VL of 62.5 m −1 , a higher volumetric mass transfer coefficient k La of 155.16 h −1 can be achieved. 116 In other types of reactors, such as BCRs, the most important parameters that are considered include gas and liquid phase concentrations, whereas in CSTRs, the specic gas uptake, cell retention time, ethanol and acetic acid concentration, cell concentration, CO 2 conversion efficiency, and H 2 conversion efficiency are important parameters. Different studies have been carried out to use different modeling approaches to study these parameters to solve the main bottlenecks of syngas fermentation.…”
Section: Ljungdahlii 112mentioning
confidence: 99%
“…As the uctuations in the pressure through the hollow ber lumen and the membrane's surface area per unit working volume of the liquid inuence the gas-liquid k La , 115 a study has reported that with a lower pressure of 37.23 kPa and a larger membrane surface area per unit working volume AS/VL of 62.5 m −1 , a higher volumetric mass transfer coefficient k La of 155.16 h −1 can be achieved. 116 In other types of reactors, such as BCRs, the most important parameters that are considered include gas and liquid phase concentrations, whereas in CSTRs, the specic gas uptake, cell retention time, ethanol and acetic acid concentration, cell concentration, CO 2 conversion efficiency, and H 2 conversion efficiency are important parameters. Different studies have been carried out to use different modeling approaches to study these parameters to solve the main bottlenecks of syngas fermentation.…”
Section: Ljungdahlii 112mentioning
confidence: 99%
“…Abubackar et al 46 highlighted a few challenges in the commercialization of bioethanol production using gas (syngas and waste gas) fermentation, which include feedstock properties and preparation, fermentation media, gas-liquid mass transfer, product recovery and production costs. Owoade et al 47 reviewed the syngas fermentation process for bioethanol production and mentioned that the quality of fermented syngas is dependent on many factors such as bacteria species, bioreactor type, syngas composition, operational parameters and gas-liquid mass transfer rate. It was suggested that using genetically modified strains, suitable fermentation media, efficient process control and optimal bioreactor design would enhance product generation and lower production costs.…”
Section: Propertiesmentioning
confidence: 99%
“…The production of ethanol using fermentation exhibits greater carbon utilization and selectivities compared to the direct chemical conversion of syngas to ethanol with catalysts (Badgett et al, 2021). Furthermore, LanzaTech also partnered with the U.S. Department of Energy's national laboratories to upgrade the produced ethanol into aviation fuels through catalytic conversion (Badgett et al, 2021;Owoade et al, 2023), which manifests the implementation of multimodality strategy by utilizing multiple unit operation to achieve otherwise unattainable goals in producing complex end products.…”
Section: Case 4 Multimodal Unit Operations For Syngas To Ethanol At C...mentioning
confidence: 99%
“…It is noteworthy that in addition to LanzaTech, there are several other organizations-including Ineos Bio (Vero Beach, FL, USA), Coskata (Warrenville, IL, USA), Genomatica (San Diego, CA, USA), and Kiverdi (Pleasanton, CA, USA)-that are also working toward the commercialization of syngas fermentation for the production of ethanol and other chemicals, as discussed in a recent review (Owoade et al, 2023).…”
Section: Case 4 Multimodal Unit Operations For Syngas To Ethanol At C...mentioning
confidence: 99%